2013
DOI: 10.1371/journal.pone.0065627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravitreal Methotrexate and Rituximab on Interleukin-10 Levels in Aqueous Humor of Treated Eyes with Vitreoretinal Lymphoma

Abstract: Intraocular cytokines are promising diagnostic biomarkers of vitreoretinal lymphoma. Here, we evaluate the utility of IL-10, IL-6 and IL-10/IL-6 for discriminating lymphoma from uveitis and report the effects of intraocular methotrexate and rituximab on aqueous cytokine levels in eyes with lymphoma. This is a retrospective case series including 10 patients with lymphoma and 7 patients with uveitis. Non-parametric Mann-Whitney analysis was performed to determine statistical significance of difference in interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 19 publications
4
36
1
2
Order By: Relevance
“…An IL-10:IL-6 ratio 41.0 is highly suggestive of PVRL [15][16][17] and this can be measured in the vitreous fluid as well as in the aqueous humor due to diffusion of interleukins from the posterior to the anterior chamber. 18 Even though the determination of IL-10 and IL-6 concentration in the anterior chamber appears to have insufficient sensitivity and specificity to be used as the sole diagnostic tool, 19 we have recently demonstrated that IL-10 concentration in aqueous humor correlates with disease activity and therefore may be useful to evaluate the effect of treatment in PVRL 20 .…”
mentioning
confidence: 99%
“…An IL-10:IL-6 ratio 41.0 is highly suggestive of PVRL [15][16][17] and this can be measured in the vitreous fluid as well as in the aqueous humor due to diffusion of interleukins from the posterior to the anterior chamber. 18 Even though the determination of IL-10 and IL-6 concentration in the anterior chamber appears to have insufficient sensitivity and specificity to be used as the sole diagnostic tool, 19 we have recently demonstrated that IL-10 concentration in aqueous humor correlates with disease activity and therefore may be useful to evaluate the effect of treatment in PVRL 20 .…”
mentioning
confidence: 99%
“…Intravitreal drugs targeting different cytokines for the treatment of local inflammation in chronic non-infectious uveitis have given promising results. [34][35][36][37][38] Identification of the cytokines involved in the pathogenesis of different OIs in HIV-infected individuals has important implications for the development of drugs targeting these cytokines, particularly in cases of persistent inflammation after successful treatment of active ocular infections.…”
Section: Discussionmentioning
confidence: 99%
“…Einige Zentren setzen sich für die Bestimmung der Zytokinlevel innerhalb der okulären Flüssigkeiten ein, um eine weitere diagnostische Hilfestellung zur Zytologie mit Nachweis oder Ausschluss der PVRL zu erhalten [2, 51,55,56,57,58,59,60]. Dies betrifft das Kammerwasser und die Glaskörperflüssigkeit.…”
Section: Tab 2)unclassified
“…Der exakte Wert für die IL-10-Konzentration oder die IL-10:IL-6-Ratio variiert zwischen den verschiedenen Laboratorien hauptsächlich wegen der Unterschiede der angewendeten Methoden und der unterschiedlichen Konditionen in der Probengewinnung, der Techniken und der Gerätschaften, die zur Bestimmung benutzt werden, einschließlich der (bekannten oder nicht bekannten) Verdünnung der Glaskörperproben und der eigenen Laborerfahrung. Interleukinwerte und -verhältnis wurden auch während der Therapie als Krankheitsverlaufsmarker eingesetzt [57,59,60].…”
Section: Tab 2)unclassified